Lyme Disease: antibodies against Borrelia burgdorferi in farm workers in Argentina - Stanchi Nestor Oscar; Balague Laura Josefina (Revista de Saúde Pública, 1993)
Lyme Disease is a tick-borne (specially by Ixodes ticks) immune-mediated inflammatory disorder caused by a newly recognize spirochete, Borrelia burgdorferi. Indirect fluorescent antibody (IF) staining methods and enzyme-linked immunosorbent assay are frequently relied upon to confirm Lyme borreliosis infections. Although serologic testing for antibodies has limitations, it is still the only practical means of confirming B. burgdorferi infections. Because we have no previous report of Lyme disease in human inhabitants in Argentina, a study was designed as a seroepidemiologic investigation of the immune response to B. burgdorferi in farm workers of Argentina with arthritis symptoms. Three out of 28 sera were positive (#1,5 and 9). Serum # 1 was positive for Immunoglobulin G at dilution 1:320, serum # 5 and # 9 both to dilution 1:160; while for Immunoglobulin M all (#1, 5 and 9) were positive at low dilution (1:40) using IF. The results showed that antibodies against B. burgdorferi are present in an Argentinian population. Thus caution should be exercised in the clinical interpretation of arthritis until the presence of B. burgdorferi be confirmed by culture in specific media.